Changes in reef fish assemblages in a cross-shelf euphotic-mesophotic gradient in tropical SW Atlantic. (30th September 2021) - Silva, M.B.; Rosa, R.S.; Menezes, R.; Francini-Filho, R.B.
Abstract: Despite a vast number of studies about shallow reef fish assemblages, and an increasing amount of studies about mesophotic ones, there are very few cross-shelf assessments including both, shallow and mesophotic depths. Herein, we analyze changes in reef fish assemblages in a cross-shelf euphotic-mesophotic (19–72.6 m) gradient in tropical SW Atlantic. Data was obtained using a novel low-cost 360° stationary video system. Sixty-four species from thirty families were identified. Depth, distance offshore and proportion of consolidated substrate were the main predictors of fish assemblages' structure. Four distinct fish assemblages were identified across the depth gradient (20–30, 30–40, 40–50 and 50–75 m), with marked shifts in composition, abundance, and trophic structure. Abundance of invertebrate feeders and large roving herbivores declined across the shelf and with increasing depth, while abundance of planktivores and piscivores increased, particularly below 50 m. These changes were likely caused by changes in food availability and habitat suitability. Our low-cost video system yielded high-resolution images that enabled us to accurately survey reef fish assemblages, being therefore a useful method for studies focusing on both, euphotic and mesophotic reef ecosystems. Our results contribute to a better understanding of how reef fish assemblages change with increasing depth in SW Atlantic reefs and corroborate the idea that the breakpoint between euphotic and mesophotic fish assemblages is context-dependent rather than previously defined as 30 m depth. Highlights: We assessed changes in reef fish assemblages in a cross-shelf euphotic-mesophotic gradient in tropical SW Atlantic. Data were collected using a novel low-cost 360° video census system. Distinct fish assemblages were recorded across the shelf in four different depth strata (20–30, 30–40, 40–50, and 50–75 m). Fish assemblages changed abruptly at 50 m due to replacement of herbivores and invertivores by planktivores and carnivores.